Enhancing Students’ Vocabulary Through Story Telling - Erniyanti Nur Fatahhela Dewi; Nindya Hasanah; Muhammad Faishol Nurul Huda (CV. Eureka Murakabi Abadi, 2022)
Storytelling is a practical and powerful teaching tool, especially for language learning. The current study is aimed to obtain empirical evidence about the effectiveness of using storytelling on students' vocabulary achievement of describing things around us. In this regard, the population was seventh-grade students of SMP PGRI 1 Ciputat. Moreover, the study sample consisted of 25 students from the VII-7 class in the Experimental Group and 25 students from VII-8 in the controlled group. The research instrument was a test that consisted of pretest and post-test forms. The technique used in collecting data was quantitative with t-test. The result of this study showed that the use of storytelling is effective on students' vocabulary. It can be seen from the result of the calculation that the students' score in the experimental class was higher than controlled class. Based on the calculation of the t-test that Ho was rejected and Ha was accepted as formulated if to > tt. Based on the calculation, the result of to was higher than tt, which was 2.778 > 2.021. It can be concluded that the students who learn vocabulary using storytelling had a significant effect on vocabulary compared to those who did not learn vocabulary by using storytelling.